Are Pension Plans Investments Popular? Evidence From Investors’ Intention Survey In India - Pushpa B V (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The real income of people in India has gained momentum after 1992 mainly because of pedestal provided by the government & changing demographic trends in the globe. The markets, institutions, products, and savings began to expand to earn a better return on their savings portfolios. Pension schemes play a seminal part in the flow of income after superannuation. There are two categories of pension plans in India the Defined Benefit and Defined Contribution plan. An evaluation of pension plans using secondary data revealed that average returns based on market stipulation is less than that of the returns from Defined Benefit plans. Pension schemes launched by LIC of India & other insurance companies were not attractive & hence did not take off. The pension plans with possible options did not yield returns as Mutual funds or market-based funds. A survey was carried out in order to understand intention of customers/investors towards savings and investment in pension plan also to know reasons for non acceptance of the same. The study collects primary data from 134 respondents / investors using Cue sampling method from a structured questionnaire. The results of the study highlight that pension are still considered as secondary preference as against savings for immediate liquidity and long term asset funds. While pension is a necessity at the core of the consumer adequacy of returns, long term size of savings, income adequacy, cost of pension schemes, low awareness, lack of perceived transparency and higher investment spending under exceptional and normal situation contribute to low level of acceptance of pension plans and schemes.